Knowledge Management System pada Biro Administrasi Akademik Akademi Pariwista Nusantara - Yudi Akbar (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2018)
Knowledge Management System (KMS) aims to improve the quality of human resources in an organization by improving communication among employees and to increase skill by transferring knowledge. Knowledge Management System (KMS) is one of many ways to foster a culture of knowledge sharing among individuals and organizations. In this research, the researcher tries to develop a model of knowledge management system suitable for existing condition at the Academic Administration Bureau of Nusantara Tourism Academy. The method used in this research is SSM model framework, while the knowledge is formed using SECI model. The system is designed by using Unified Modeling Language (UML) method. The functional system is tested using using FGD method with success rate of 90% and software quality is tested using MCcall's method with success rate of 87.75%. The result of this research is the Knowledge Management System prototype that can be a solution to share knowledge because it can properly record the employees’ knowledge and experience and can support the employees’ performance at Academic Administration Bureau of Nusantara Tourism Academy.